¬Identifikasi Peranan Sektor Basis dan Tingkat Aksesibilitas Dalam Meningkatkan Pertumbuhan Ekonomi Kabupaten Jayapura - Gina Renatha (Jurusan Ilmu Ekonomi Universitas Katolik Parahyangan, 2022)
This study determine the basic sector of Jayapura Regency which can be a driver of economic growth period 2015-2017. This study identified sub-districts that have the most advantageous position in terms of accessibility. The results of the study using the LQ, DLQ, and multiplier effect approaches found that the agriculture, forestry and fisheries sectors were the sectors that could have the greatest influence on the formation of GRDP in Jayapura Regency. In addition, based on the calculation of the Connectivity Quotient (CQ), Raveni Rara District is the sub-district with the most advantageous position in terms of level of access and for interaction between sub-districts in Jayapura Regency.